Tourism Preferences of Gen Z in the Philippines: A Conjoint Analysis of Beach Resort Attributes in Samal Island - Sumatra, Emmanuel Joseph (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the beach resort preferences of Generation Z college students from Davao City, Philippines, based on data from 876 respondents. Using conjoint analysis, the study explores how various resort attributes influence their decision-making for Samal Island, a popular coastal destination. The results reveal that water activities and swimming pool availability are the most important factors in resort selection, with advanced water activities such as jet ski rentals and banana boat rides receiving the highest preferences. The study provides actionable insights for resort operators, recommending a focus on offering adventurous, immersive experiences, comfortable amenities, and personalized services to attract Gen Z travelers. Additionally, the findings suggest incorporating sustainability and digital innovation into resort offerings and marketing strategies, as these factors resonate with eco-conscious and digitally connected Gen Z. This research contributes to tourism marketing and sustainable coastal tourism practices.